A COMPREHENSIVE REVIEW ON PRONIOSOMES: A NEW CONCEPT IN OCULAR DRUG DELIVERY - PATEL, AKHILESH; HAVELIKAR, UJWAL; SHARMA, VIPIN; YADAV, SUCHITRA; RATHEE, SAKSHI; GHOSH, BINITA; GILL, KARTIK; SINGH, GAMDHUR; SHARMA, LALIT; KOLAY, ARINDAM KOLAYARINDAM (International Journal of Current Pharmaceutical Research, 2023)
The concept of novel drug delivery with the comparison of modern and conventional delivery system. The Ocular is the most challenging organ to deliver drugs after the brain and conventional delivery systems currently available in the arsenal have severe limitations thus there is a strong demand for an improved ocular delivery system and a suitable opinion is a novel drug delivery system. Noisome and liposome are dominant vesicular carriers in ocular drug delivery, as both systems improve the bioavailability of drugs and are well tolerated in ocular; however, both delivery systems have critical drawbacks of physicochemical stability during storage, lacking contain in dispersion and fusion of nanoparticles. The gel form is formulated by the coacervation phase’s parathion method. The material utilized for the formulation of proniosomes are non-ionic surfactant, cholesterol, carrier and alcohol are well tolerable and nontoxic in the ocular. The benefits offered to ocular drug delivery are prolonged retention time of formulation on the ocular surface, enhance ocular penetration to deliver effective therapeutic dosage, improve bioavailability of hydrophobic, lipophilic and herbal drugs, biocompatible, biodegradable, nontoxic and stable stored in pro-vesicle state. Hereby article will review proniosomes drug delivery from the perspective of ophthalmic delivery, discussing proniosomes as an ocular carrier, materials and methods their effect on ocular drug delivery and depth explanation of recent studies of proniosome in the ocular. Proniosomes are one of the sterile drug delivery systems that have seen a tremendous increase in popularity and are heavily utilized in cancer therapy. Researchers and academicians generally agree that incorporating the medicine into niosomes will improve its ability to target tissues where it is needed. Proniosomes created by academics and researchers. Niosomes that are produced from protostomes are a promising medication delivery system. They are well known for avoiding several issues related to aqueous noisome dispersion as well as issues with physical stability such aggregation, fusion, and leakage. They make transportation, distribution, storage, and dosage even more convenient. Proniosomes not only present a promising medication delivery method but also have the potential to speed up the skin barrier's repair.